The mediating role of financial in the relationship between expenditure structure and financial performance of local colledges and universities in China - Hou, Yu Yan (Tanjong Malim, 2024)
The mediating role of financial in the relationship between expenditure structure and financial performance of local colledges and universities in China by Hou, Yu Yan